Neuroanatomy for the neuroscientist - Jacobson, Stanley (Springer Science+Business Media, 2011)
Neurology, more than any other system of medicine, is rooted in the firm knowledge of basic science material (i.e., the anatomy, physiology, and pathology of the nervous system). This material enables students to readily arrive at diagnoses and to apply their knowledge to solving problems in clinical situations. Neuroanatomy for the Neuroscientist gives neuroscientists the tools to teach this material at levels appropriate for students at several levels of study, including undergraduate, graduate, dental, and medical school. The text also provides an updated approach to lesion localization in neurology, utilizing the techniques of computerized axial tomography (CT scanning), magnetic resonance imaging (MRI), and magnetic resonance angiography (MRA). Multiple illustrations demonstrating the value of these techniques in clinical neurology and neuroanatomical localization have been provided.